A dor invisível: desvelando experiências de sofrimento emocional de homens heterossexuais que vivem com HIV/Aids - Silva, Kiara Cardoso da (2019)
Among improvements, setbacks and resurfacings aids poses a challenge to civil society and academic and scientific communities, presenting itself as a public health worldwide problem which demands reflection, coping strategies and participation of the actors involved. It is a disease characterized by a serious dysfunction of the immune system infected by the HIV as the TCD4+ lymphocytes are destroyed (Brasil, 2008). The number of infected people in Brazil has risen again (UNAIDS, 2016) and the detection rates among men in the last ten years has shown a tendency of growth (Brasil, 2018). Studies about men and masculinities have gained relevance in what concerns gender in the last two decades in the country and the focus on the relation man-health has been a point of interest in the academic environments and service contexts. In this sense, this study intends to understand experiences of emotional suffering of heterosexual men self-referred as HIV/Aids positive. We conducted a qualitative research with the collaboration of 4 men ages between 20 and 49 being attended to at the Specialized Assistance Service in HIV/Aids at the Giselda Trigueiro Hospital, located in Natal/RN. The study was based on the Gadamerian Hermeneutics and the Narrative Interview using Projective Scenes used as tool. Through the dialogue with the narratives we came up with the following chapters: The construction of masculinities, which addresses this process understanding it based on a socio-historical perspective. The meaning of what it is to be a man revealed the coexistence among hegemonic standards and new masculinities; HIV/Aids: a history of fears and prejudice in which we bring the history of aids and the meaning of it to the collaborators, shifting between fear of death and of prejudice; Living with HIV/Aids: when hell is other people one must keep their secret until the end, in which we discuss the self-righteous and prejudiced view cast on PLWHA, generating their obsession with the secret of their condition, the pain of selfimposed loneliness and other fears (become sick and be discovered), besides coping strategies (use of drugs, work, humor, music, keeping the secret and the matter of spirituality and religiosity); Psychology and the PLWHA: between ignorance, care and the ethical-political commitment, in which we address the relation between psychology and the PLWHA, approaching the unfamiliarity with this knowledge/activity and the access of men to psychology services, as well as addressing the (un)known necessities and unseen hardships in the psychology care, ending with the reflection on the clinical and ethical-political commitment in face of the challenges posed by this scenario. By problematizing questions related to these men’s experiences, this study makes specificities of the emotional suffering they live visible and reveals their necessity of care, contributing to the promotion of a psychology that is ethically and politically engaged with the assistance given to the PLWHA, aiming to break excluding and stigmatizing paradigms in order to establish solidarity, welcoming and appreciation of these lives, not letting them perish by discrimination and stigmatization. We hope to contribute to promote a committed psychology that walks towards the building of stronger bonds that recognize the right to be different. Acts based on these principles produce life!